La axiología educativa para la formación de una cultura ética en los estudiantes de octavo año de básica superior de la unidad educativa “Quintiliano Sánchez Rendón”, cantón buena fe, periodo 2021-2022 - Arteaga Ponce, Eliana María (2021)
Educational axiology is the study of values from a pedagogical point of view. The research project called "The Educational Axiology for the formation of an Ethical Culture in the eighth-year students of upper basic of the Quintiliano Sánchez Rendón Educational Unit", the objective proposed in this study was to develop a pedagogical project in education in values, that fosters the school for parents. It was based on the mixed model (qualitative and quantitative), its type of research was applied and bibliographic, where the purpose was to solve precise and practical problems, it also provides necessary theoretical knowledge, which allowed observing the participation of the members of the Educational Community formed by teachers, students and parents, in the face of treatment in daily life. To collect information, a survey was applied to the students, as well as the respective interview with parents and teachers, which contributed to the verification if the behavior of the students affects the teaching-learning process, at the end of this research I have achieved observe the degree of involvement of family members in the development of values that allow coexistence, to achieve this a series of training workshops on a school for parents is proposed, where it is focused on counteracting the discipline or behavior of the learners. The results of the surveys and interviews applied to each of the members of the Educational Community are also included with an action to contribute to the development and strengthening of relationships that exist in society.